Prevalence of bacteremia among children complaining different kinds of infections under 12 years old in Baghdad (Baghdad Science Journal, 2011)
This study was designed to determine the percentage and the main causative agent causing bacteremia among children aged up to 12 years and complaining from different types of infections (Respiratory, intestinal, and urinary tract infection) in Baghdad. Results showed that the percentage of infection was 46.19 % the main causative agents were Enterobacteriaceae including (E.coli , Pseudomonas , Salmonella.typhi .Serratia , Enterobacter , Klebsiella )and other than Enterobacteriaceae which includes(Staph.aureus , Staph.epidermidis , Streptococcus.Pneumonia and ?-hemolytic streptococci ) .Regarding the age factor ,results showed that the highest infection rate was among the age group (1 day-12 month ) and (12 -36month ) (64.89%)and (15.95%)respectively while the lowest was in (61 month – 12 years )and (37 -60 month) (12.76%) and( 6.38) respectively . All bacterial strains isolated from patient were submitted to sensitivity test, results showed various reactions towards different types of antibiotics used in this study.